2019
DOI: 10.1111/1759-7714.13217
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of lung cancer with adjacent lobe invasion in relation to fissure integrity

Abstract: Background: Tumor with adjacent lobe invasion (T-ALI) is an uncommon condition. Controversy still exists regarding the optimal resection of adjacent lobe invasion, and the prognostic value in relation to fissure integrity at the tumor invasion point. The aims of this paper were to evaluate the prognosis of T-ALI with regard to fissure integrity, and type of resection. Methods: This was a retrospective multicenter study which included all consecutive patients with T-ALI undergoing surgical treatment. Based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, Haam et al 26 reported the OS and disease‐free survival of ALI‐NSCLC patients were similar to those of T3, and considered the T category should be classified as T3 rather than T2. Andreetti et al 27 differentiated the ALI‐NSCLC as complete and incomplete ALI, based on whether the tumor invaded the adjacent lobe across a complete fissure point, and found the latter provided a better prognosis. Meanwhile, Ohtaki et al 28 divided ALI into the invasion across complete and incomplete fissures, and found the complete fissure was associated with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, Haam et al 26 reported the OS and disease‐free survival of ALI‐NSCLC patients were similar to those of T3, and considered the T category should be classified as T3 rather than T2. Andreetti et al 27 differentiated the ALI‐NSCLC as complete and incomplete ALI, based on whether the tumor invaded the adjacent lobe across a complete fissure point, and found the latter provided a better prognosis. Meanwhile, Ohtaki et al 28 divided ALI into the invasion across complete and incomplete fissures, and found the complete fissure was associated with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Andreetti et al analyzed 135 patients with cancers involving the adjacent lobe and also found statistically significant differences between the 5-year survival rates of those patients with direct invasion and with invasion across a complete fissure: 63.9 and 48.9%, respectively ( p = 0.01). In addition, they found significantly higher rates of nodal disease (35 and 4%, p = 0.004) and recurrence (43 and 16%, p = 0.01) among patients with invasion across a complete fissure [ 17 ].…”
Section: Data-based Innovations Of the 7th And The 8th Edition Of The Tnm Classificationmentioning
confidence: 99%
“…Data on the topic are scarce, but Okada et al did not find significant differences in the survival of 10 patients who had undergone peumonectomy or bilobectomy and 9 who had undergone lobectomy and sublobar resection of the involved adjacent lobe ( p = 0.9115) [ 15 ]. Andreetti et al did not find statistically significant differences between the 5-year survival rates of pneumonectomy, bilobectomy, lobectomy with segmentectomy, or lobectomy with wedge resection: 39.8, 53.9, 54.3, and 59.8%, respectively ( p = 0.09) [ 17 ]. From these two reports, it seems that a sublobar resection of the involved adjacent lobe could be an adequate oncologic operation.…”
Section: Data-based Innovations Of the 7th And The 8th Edition Of The Tnm Classificationmentioning
confidence: 99%